ABC Algorithm for Combinatorial Testing Problem - Alsewari, Abdulrahman A.; Alazzawi, Ammar K.; Rassem, Taha H.; M. Nomani, Kabir; Homaid, Ameen A. Ba; Alsariera, Yazan A.; Tairan, Nasser M.; Kamal Z., Zamli (Malaysian Journal Management System, 2017)

(untitled)
Computer software is in high demand everywhere in the world. The high dependence on software makes software requirements more complicated. As a result, software testing tasks get costlier and challenging due to a large number of test cases, coupled with the vast number of the system requirements. This challenge presents the need for reduction of the system redundant test cases. A combinatorial testing approach gives an intended result from the optimization of the system test cases. Hence, this study implements a combinatorial testing strategy called Artificial Bee Colony Test Generation (ABC-TG) that helps to get rid of some of the current combinatorial testing strategies. Results obtained from the ABC-TG were benchmarked with the results obtained from existing strategies in order to determine the efficiency of the ABC-TG. Finally, ABC-TG shows the efficiency and effectiveness in terms of generating optimum test cases size of some of the case studies and a comparable result with the existing combinatorial testing strategies.